A revision of the Hoya uncinata complex (Apocynaceae, Asclepiadoideae), with description of a new species - Rodda, Michele; Rahayu, Sri (Phytotaxa, 2018)
The Hoya uncinata complex is a group of species with clear latex, deeply lobed rotate corolla and corpusculum of the pollinarium almost as large as the pollinium. Three species are included in the complex: Hoya uncinata from Java and Sumatra, Hoya ruthiae from Borneo and a new species here described, Hoya corneri, from Borneo, Peninsular Malaysia and Thailand. Hoya padangensis is recognised as a new synonym of H. uncinata. Hoya padangensis and H. uncinata are typified.